The Combination Therapy with Zoledronic Acid and Propranolol Improves the Trabecular Microarchitecture and Mechanical Property in an Rat Model of Postmenopausal Osteoporosis - Deepak Kumar Khajuria; Rema Razdan; D. Roy Mahapatra (Journal of Osteoporosis)
We conducted the present study to investigate the therapeutic effects of propranolol (PRO), alone and in combination with the antiresorptive agent ZOL, in a rat model of postmenopausal osteoporosis. Female Wistar rats were OVX or sham-operated at 3 months of age. Twelve weeks after surgery, rats were randomized into six groups: (1) sham + vehicle, (2) OVX + vehicle, (3) OVX + ZOL (100 μg/kg, i.v. single dose), (4) OVX + ZOL (50 μg/kg, i.v. single dose), (5) OVX + PRO (0.1 mg/kg, s.c. 5 days per week), and (6) OVX + ZOL (50 μg/kg, i.v. single dose) + PRO (0.1 mg/kg, s.c. 5 days per week) for 12 weeks. At the end of treatment study, various bone parameters were evaluated. With respect to improvement in the mechanical strength of the lumbar spine and the femoral mid-shaft, the combination treatment of ZOL and PRO was more effective than each drug administered as a monotherapy. Moreover, combination therapy using ZOL and PRO preserved the trabecular microarchitecture better than single-drug therapy using ZOL or PRO in OVX rats. These data suggest that combination therapy with ZOL plus PRO represents a potentially useful therapeutic option for patients with osteoporosis.